Anemia is an independent prognostic factor in intracerebral hemorrhage: an observational cohort study - Kuramatsu, Joji B (BioMed Central, 2013)
INTRODUCTION: To date only two studies have evaluated anemia status in acute intracerebral hemorrhage (ICH) reporting that on admission anemia (OAA) was associated with larger hematoma volume, and lower hemoglobin levels during hospital stay, which related to poorer outcome. The question remains whether anemia influences outcome through related volume-effects or itself has an independent impact? METHODS: This single-center investigation included 435 consecutive patients with spontaneous ICH admitted to the Department of Neurology over five years. Functional short- and long-term outcome (3 months and 1 year) were analyzed for anemia status. Multivariate logistic and graphical regression analyses were calculated for associations of anemia and to determine independent effects on functional outcome. It was decided to perform a separate analysis for patients with ICH-volume <30cm(3 )(minor-volume-ICH). RESULTS: Overall short-term-outcome was worse in anemic patients (mRS[4-6] OAA = 93.3% vs. non-OAA = 61.2%, P < 0.01), and there was a further shift towards an increased long-term mortality (P = 0.02). The probability of unfavorable long-term-outcome (mRS[4-6]) in OAA was elevated 7-fold (OR:7.5; P < 0.01). Receiver operating characteristics curve (ROC) analysis revealed a positive but poor association of ICH-volume and anemia (AUC = 0.67) suggesting volume-undriven outcome-effects of anemia (AUC = 0.75). Multivariate regression analyses revealed that anemia, besides established parameters, has the strongest relation to unfavorable outcome (OR:3.0; P < 0.01). This is even more pronounced in minor-volume-ICH (OR:5.6; P < 0.01). CONCLUSIONS: Anemia seems to be a previously unrecognized significant predictor of unfavorable functional outcome with independent effects beyond its association with larger hemorrhage volumes. The recognition of anemia and its treatment may possibly influence outcome after ICH and as such prospective interventional studies are warranted.